Study guides

☆☆

Q: What is the answer to 3 plus 3n equals 9 plus 2n plus 4n?

Write your answer...

Submit

Still have questions?

Related questions

3n + 2n = 7 + 4n 5n = 7 + 4n 5n - 4n = 7 n = 7

It is 12n2 + 3n - 58

4n-8=3n+2 4n=3n+2+8 4n=3n+10 4n-3n+10 n=10 N = 10

Move the 2n over the equals sign. Become 4n (as 6n-2n= 4n) and then if 4n=16 then n=4.

12+4n = 2n12+4n-4n = 2n-4n12 = -2n-1/2(12 = -2n)-6 = n

3n+18 = 39 -4n 3n+4n = 39 -18 7n = 21 n = 3

4n

4n + 3y

3n + 4n = 42 7n = 42 n = 42/7 n = 6

3n + 4n = -14 7n /7 = -14 /7 n = -2

6n - 2n + 2 = n - 11 4n - n = -11 - 2 3n = -13 n = -13/3 = -4.3333

2n+2n equals 4n

n= -2

4n

4n - 2n = 84 2n = 84 n = 42

6n - 4 - 3 = 3n + 10 + 4n -7 = 7n - 6n + 10 -17 = n

3n

The question seems ambigous, but I will consider n 2n to be solving for n:2n - 3n = n/3 + 14-n = n/3 + 14-3n = n + 42-4n = 42Thus, the solution is n = -42/4 = -21/2 = -10.5.

3n - 9 + 4n = 8nCombine like terms:7n - 9 = 8nSubtract 7n from both sides:-9 = n

Subtracting 3n from each side gives 12 = 4n or 4n = 12. n = 12/4 n = 3

This can be solved by grouping all terms with "n" in them on one side of the equation, and all other terms on the opposite side, then adding together like terms, and dividing both sides by the remaining coefficient of "n": n - 16 = 2n + 12 + 3n ∴ n - 2n - 3n = 12 + 16 ∴ -4n = 28 ∴ n = -7

(4n + 1)*(2n + 6) = 8n2 + 26n + 6

4n - 2n = 18 Therefore, 2n = 18 Therefore, n = 18/2 = 9

4n

As follows:- 4n+13 = n-8 4n-n = -8-13 3n = -21 n = -7